Lung transplantation: Chronic allograft dysfunction and establishing immune tolerance - Gracon, Adam S.A. (Hum Immunol, 2014)
Despite significant medical advances since the advent of lung transplantation, improvements in long-term survival have been largely unrealized. Chronic lung allograft dysfunction, in particular obliterative bronchiolitis, is the primary limiting factor. The predominant etiology of obliterative bronchiolitis involves the recipient’s innate and adaptive immune response to the transplanted allograft. Current therapeutic strategies have failed to provide a definitive treatment paradigm to improve long-term outcomes. Inducing immune tolerance is an emerging therapeutic strategy that abrogates allograft rejection, avoids immunosuppression, and improves long-term graft function. The aim of this review is to discuss the key immunologic components of obliterative bronchiolitis, describe the state of establishing immune tolerance in transplantation, and highlight those strategies being evaluated in lung transplantation.